Impact of nutritional support that does and does not meet guideline standards on clinical outcome in surgical patients at nutritional risk: a prospective cohort study. Issue 1 (December 2015) - Sun, Da-Li; Li, Wei-Ming; Li, Shu-Min; Cen, Yun-Yun; Lin, Yue-ying; Xu, Qing-Wen; Li, Yi-Jun; Sun, Yan-Bo; Qi, Yu-xing; Yang, Ting; Lu, Qi-Ping; Xu, Peng-Yuan
Abstract Objective To investigate the impact of nutritional support on clinical outcomes in patients at nutritional risk who receive nutritional support that meets guideline standards and those who do not. Methods This prospective cohort study enrolled hospitalized patients from the Second Affiliated Hospital of Kunming Medical University from February 2010 to June 2012. The research protocols were approved by the university's ethics committee, and the patients signed informed consent forms. The clinical data were collected based on nutritional risk screening, administration of enteral and parenteral nutrition, surgical information, complications, and length of hospital stay. Results During the study period, 525 patients at nutritional risk were enrolled in the cohorts. Among patients who received nutritional support that met the guideline standards (Cohort 1), the incidence of infectious complications was lower than that in patients who did not meet guideline standards (Cohort 2) (17.1 % vs. 26.9 %, P = 0.01). Subgroup analysis showed that individuals who received a combination of parenteral nutrition (PN) and enteral nutrition (EN) for 7 or more days had a significantly lower incidence of infectious complications (P = 0.001) than those who received only PN for 7 or more days or those who received nutritional support for less than 7 days or at less than 10 kcal/kg/d. Binary logistic regression analysis showed that, after adjusting for confounding factors, nutritional support that met guideline standards for patients with nutritional risk was a protective factor for complications (OR: 0.870, P < 0.002). Conclusions In patients at nutritional risk after abdominal surgery, nutritional support that meets recommended nutrient guidelines (especially regimens involving PN + EN ≥ 7 days) might decrease the incidence of infectious complications and is worth recommending; however, well-designed trials are needed to confirm our findings. Nutritional support that does not meet the guideline standards is considered clinically undesirable.